Assessing the flexion behavior of bolted rail joints using finite element analysis. (October 2019) - Samantaray, S.K.; Mittal, S.K.; Mahapatra, P.; Kumar, Sanjeev
Abstract: The weakest component in the railway track structure is rail joint. It is one of the safety acute joints available which provided a break in continuity of the rail track. It connected the two ends of the rail with nut and bolt to achieve mechanical and functional requirements of smooth running of the train. Due to increase in traffic density, rail joints are subjected to high axle load. As structure bolted joint, it become most vulnerable parts in railway track. In this paper, three-dimensional Finite Element Analyses (FEA) of bolted rail joints is carried out to study the structural integrity and deflection performance of rail bolted joint bars under static loading conditions. The rail joint has been investigated under different loading conditions and stress distribution at the joint bars and nuts & bolts region to understand the behavior. This paper also presents an analysis of bolted joints with specific attention to quantify deformation and to the effect of the looseness of bolted joint to structural behavior. The effect of nuts & bolt looseness and deformation characteristics has been studied to improve the performance and life expectancy of the rail joints. Highlights: Designing and study of 3D finite element model of rail joint structure. Analysed the structural integrity and deflection performance of rail joint bars with static loading conditions. Investigated the Stress analysis and flexion behavior of bolted rail joint. Analysed the bolted rail joints with particular attention to quantify deformation and to the effect of the loose of bolt on structural behavior of rail joint.